Existence Results for a px-Kirchhoff-Type Equation without Ambrosetti-Rabinowitz Condition. (30th May 2013) - Wang, Libo; Pei, Minghe
Abstract : We consider the existence and multiplicity of solutions for the p x -Kirchhoff-type equations without Ambrosetti-Rabinowitz condition. Using the Mountain Pass Lemma, the Fountain Theorem, and its dual, the existence of solutions and infinitely many solutions were obtained, respectively.